Examining the use of Alternative performance measures (Non-IFRS Measures) in comparing financial performance of listed companies - Mtangi, Munyaradzi (Midlands State University, 2017)
The research was conducted to identify whether Alternative Performance Measures (NonIFRS Measures) could be used by external stakeholders to compare financial performance of corporate entities listed on the Zimbabwe Stock Exchange. The research was triggered by the prevalence of these additional measures of performance, which were deemed to be marring and driving away focus from the traditional financial information: the IFRS-complaint financial statements. It was perceived that the common use of these performance measures might deter the smooth comparability of financial information. Data was gathered from 10 audit clerks employed in a mid-tier auditing firm. The data collection dictated that companies calculated Alternative Performance Measures differently from one another, thereby impairing financial performance comparability. Evidence from data collection also noted that management bias was inherent in the reporting of Alternative Performance Measures. The research, however, concluded that this information was reliable and that listed counters primarily used them to re-emphasise matters already discussed in the financial statements and disclose those events and transactions that are peculiar to the firm. The researcher encouraged the engagement of external assurance providers in the verification process, to ensure that Alternative Performance Measures are reconciled to financial statements and that their quality and credibility is enhanced. He also recommended a consultative dialogue between relevant stakeholders on the responsible reporting of these measures, as he identified that the duties of individual groups of stakeholders were not clearly defined. He however discouraged the regulation of reporting the performance measures, as he discovered that many corporate Boards were experiencing regulatory fatigue from an excessive imposition of rules and standards in their